2023
DOI: 10.3390/microorganisms11102575
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Multidrug Resistance: Clinical Implications for Infection Management in Critically Ill Patients

Gamze Kalın,
Emine Alp,
Arthur Chouaikhi
et al.

Abstract: The increasing incidence of antimicrobial resistance (AMR) worldwide represents a serious threat in the management of sepsis. Due to resistance to the most common antimicrobials prescribed, multidrug-resistant (MDR) pathogens have been associated with delays in adequate antimicrobial therapy leading to significant increases in mortality, along with prolonged hospital length of stay (LOS) and increases in healthcare costs. In response to MDR infections and the delay of microbiological results, broad-spectrum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…Consequently, in the face of MDR infections and delayed microbiological results, the widespread use of broad-spectrum antibiotics in empirical antimicrobial therapy has become a common practice. However, this reliance on broad-spectrum antibiotics further risks individual health by continuing the overuse and misuse of these drugs, consequently exacerbating the development of antimicrobial resistance [230].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the face of MDR infections and delayed microbiological results, the widespread use of broad-spectrum antibiotics in empirical antimicrobial therapy has become a common practice. However, this reliance on broad-spectrum antibiotics further risks individual health by continuing the overuse and misuse of these drugs, consequently exacerbating the development of antimicrobial resistance [230].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that length of hospital or ICU stay is an important risk factor for acquiring a nosocomial MDRGN infection [ 22 , 23 ]. Moreover, infections by CRGN pathogens are associated with an increased risk of mortality [ 24 27 ]. Therefore, the present study was designed to address the question of contribution of CRGN bacterial infections in the mortality of COVID-19 critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Conventional antibiotics are becoming increasingly ineffective against a burgeoning array of resistant bacterial strains, underscoring the critical need for alternative approaches. 2 The widespread misuse and overuse of antibiotics have expedited the emergence of multidrug-resistant pathogens, 3 exemplified by notorious strains like methicillin-resistant S. aureus (MRSA) and vancomycin-resistant Enterococcus (VREF). 4,5 This proliferation of resistant strains has severely curtailed the efficacy of conventional treatments for various infections.…”
mentioning
confidence: 99%